2021
DOI: 10.1080/09537287.2021.1983661
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain traceability: a review of the benefits and its relationship with supply chain resilience

Abstract: There has been considerable recent growth in supply chain (SC) traceability research due to increased Industry 4.0 solutions and the potential of traceability systems to enable SCs to bounce back from a crisis, thereby having a long-term impact on firm/SC performance. However, to date, the relationship between SC traceability and SC Resilience (SCRes) has not been fully explored. Using a systematic literature review, this paper first provides a comprehensive state-of-the-art understanding of traceability to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 130 publications
0
28
0
1
Order By: Relevance
“…All technologies have advantages and disadvantages, and some perform better than others in certain situations depending on the product type and the requirements [ 88 ]. Findings revealed that simple or sophisticated barcodes, mass serialization, and RFID systems could all prove effective in detecting counterfeit drugs in the PSC.…”
Section: Discussionmentioning
confidence: 99%
“…All technologies have advantages and disadvantages, and some perform better than others in certain situations depending on the product type and the requirements [ 88 ]. Findings revealed that simple or sophisticated barcodes, mass serialization, and RFID systems could all prove effective in detecting counterfeit drugs in the PSC.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that BT based strategies such as flexibility, visibility and the change in network structure are the most effective strategies to fight disruption and enhance SCRES. Razak et al ( 2021 ) propounded traceability system such as BT as an enabler of SCRES. The study mentioned the direct and indirect impacts of traceability on SCRES.…”
Section: Resultsmentioning
confidence: 99%
“…For the scholars, questions to address are 1) "When is it right for the firms/organisations/entities to adopt and implement BT?” 2) “When should BT be integrated with I4.0 technologies?”. Furthermore, studies focus too much on traceability and transparency features of BT especially in food SC (Kittipanya-ngam & Tan, 2020 ; Razak et al, 2021 ). However, BT has the potential to go beyond this tracking and tracing.…”
Section: Future Research Agendamentioning
confidence: 99%
“…IS is inevitable for supply and demand visibility, essential for designing a resilient SC. Moreover, curbing information during a disaster could hamper resiliency (Hosseini & Ivanov, 2019 ; Razak et al, 2021 ). IS enhances a firm's dependability and helps overcome disruptions, the prevailing bullwhip effect, and respond to dynamic market needs (Viet et al, 2018 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%